THU0534 Joint Hypermobility in Oligoarticular Juvenile Idiopathic Arthritis. (9th June 2015) - Cecchin, V.; Sperotto, F.; Balzarin, M.; Vittadello, F.; Martini, G.; Zulian, F.
Abstract : Background: Juvenile idiopathic arthritis (JIA) is the most common chronic rheumatic disease in childhood. Oligoarticular JIA (oJIA) is the most frequent subtype of JIA, it has often lower limb involvement, ANA positivity and high risk of anterior uveitis. Objectives: Since we observed that patients with oligoarticular JIA frequently have joint hypermobility, we would like to explore if the presence of this condition may influence the clinical course, the immunologic characteristics and the outcome of oJIA. Methods: Children with oligoarticular JIA, defined by the ILAR criteria 1, followed at the Pediatric Rheumatology Unit of University of Padua, with at least two years of disease duration and complete clinical data available, have been evaluated from January to December 2014. Clinical and laboratory data at disease onset and at the last follow-up were collected. They included sex, age, presence of joint hypermobility, according to the Beighton's score 2, family history for joint hypermobility, disease activity, uveitis, ANA, treatment and outcome (Wallace criteria 3 ). Results: 274 oligoarticular JIA patients (224 F, 50 M), aged 11.5±4.5 years and followed for 6.6±3.8 years, entered the study. Age at disease onset was 4.9±3.2 years, 78.8% had persistent subtype and 21.2% extended one. Joint hypermobility was present in 72.3% of children at disease onset and in 55.8% at the last evaluation. Uveitis occurred in 20.8% and was less frequent in hypermobile children (p=0, 005). At the last examination, 52.5% of hypermobile patients were off therapy (p<0, 05) and at 5 years follow-up 51.3% were in full clinical remission, 35.4% were in clinical remission on medication and only 13.3% had active arthritis (p<0.05). Conclusions: Joint hypermobility in Oligoarticular JIA is more frequent than in normal subjects and has a positive influence on the disease course and long term outcome. References: Petty RE, Southwood TR, Manners P, et al. International League of Associations for Rheumatology classification of juvenile idiopathic arthritis: second revision, Edmonton 2001. J Rheumatol 2004;31:390-392 Beighton P, Solomon L, and Soskolne CL. Articular mobility in an African population. Ann Rheum Dis. 1973; 32: 413–418 Wallace CA, Ruperto N, Giannini E et al. Preliminary criteria for clinical remission for select categories of juvenile idiopathic arthritis. J Rheumatol. 2004;31:2290-2294 Acknowledgements: We acknowledge IL VOLO, no-profit Association for Rheumatic Diseases in Children, ONLUS, Padua, Italy for having supported the study with a dedicated grant. Disclosure of Interest: None declared